How success breeds success - Ambroise Descamps; Changxia Ke; Lionel Page (Quantitative Economics, 2022)
We investigate if, and why, an initial success can trigger a string of successes. Using random variations in success in a real-effort laboratory experiment, we cleanly identify the causal effect of an early success in a competition. We confirm that an early success indeed leads to increased chances of a later success. By alternatively eliminating strategic features of the competition, we turn on and off possible mechanisms driving the effect of an early success. Standard models of dynamic contest predict a strategic effect due to asymmetric incentives between initial winners and losers. Surprisingly, we find no evidence that they can explain the positive effect of winning. Instead, we find that the effect of winning seems driven by an information revelation effect, whereby players update their beliefs about their relative strength after experiencing an initial success.
Keywords: C91; D74; 330; confidence; Dynamic contest; experiment; feedback; momentum; real effort; Dynamic contest; momentum; real effort; feedback; confidence; experiment